Theoretical and practical modeling innovation and trends developement in the competitiveness of the market of tourist services: regional aspect - Pletsan, Hristina (Technology audit and production reserves, 2020)
The object of research is the development of competitiveness of the market of tourist services. The study is based on the development and implementation of innovations in the market of tourist services, through the prism of a new philosophy of the tourism industry, including travel, which is based primarily on safety, protection and health, growth and balance of human needs. The article highlights and substantiates the priorities of the gradual exit from the crisis of COVID-19 and trends in the competitiveness of the market of tourist services, focusing on the regional aspect. The state and main characteristics of the tourist and recreational potential of domestic tourism are analyzed, on the example of the Lviv region (Ukraine). The main negative tendencies are singled out and the ways of their solution are substantiated. The analysis of experience and perspective technologies of development of the tourist market of the region is carried out. It is characterized that the priority role in the attractiveness of the region is played by the tourist service, which forms the impression of the tourist product in general. Based on this, it is substantiated that there is a close interdependence between the service and the tourist product in the market of tourist services of Lviv region. The understanding of cultural tourism through ethno-festivals as a mechanism of development of tourist services of the Lviv region is revealed. The system of ethno-festivals of Lviv region, which provide tourist attractiveness, is singled out. It is argued that the development of cultural tourism best promotes the uniqueness of customs, rituals, traditions and culture of the region. It is proved that ethno-festivals can be considered as a mechanism of effective promotion that promotes the development of tourist services in the Lviv region. Emphasis is placed on the fact that domestic tourism and the values of sustainable development help to develop the economy and conserve resources. The mechanism optimization for improving the formation of competitiveness of the market of tourist services of the Lviv area by realization of safe tourism, development and modernization of tourist infrastructure, creation of tourist, infrastructural and innovation clusters, formation of economic logistics, active use of innovative technologies and marketing of tourist region is offered